2020
DOI: 10.1038/s41598-020-65920-2
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA_101237 promotes NSCLC progression via the miRNA-490-3p/MAPK1 axis

Abstract: Non-small cell lung cancer (NSCLC) is a common type of lung cancer, characterized by a poor prognosis. In the last several years, more and more studies have demonstrated the significant roles played by circular RNAs (circRNAs) in different human tumors progression including NSCLC. The present study was to explore the mechanism of hsa_circ_101237 in regulating non-small cell lung cancer (NSCLC). Totally 303 NSCLC cases were enrolled. A549 and H1299 cells were transfected. Cells viability, migration and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(82 citation statements)
references
References 28 publications
1
81
0
Order By: Relevance
“…microRNA-490-3p (miR-490-3p) was believed to suppress the growth of several types of cancers. It was reported that miR-490-3p could suppress glioblastoma [ 5 ], glioma [ 6 ], lung [ 7 ] and gastric carcinoma [ 8 , 9 ], breast cancer [ 10 13 ], and liver carcinoma [ 14 , 15 ]. Meanwhile, the epithelial-mesenchymal transition process could be modulated by miR-490-3p [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…microRNA-490-3p (miR-490-3p) was believed to suppress the growth of several types of cancers. It was reported that miR-490-3p could suppress glioblastoma [ 5 ], glioma [ 6 ], lung [ 7 ] and gastric carcinoma [ 8 , 9 ], breast cancer [ 10 13 ], and liver carcinoma [ 14 , 15 ]. Meanwhile, the epithelial-mesenchymal transition process could be modulated by miR-490-3p [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, circPTPRA inhibits the EMT and NSCLC cell metastasis by stimulating miR-96-5p ( Wei et al, 2019 ), while circP4HB sponges miR-133a-5p to promote NSCLC invasion and metastasis ( Hansen et al, 2013 ). Additionally, circRNA_101237 promotes NSCLC progression via miRNA-490-3p/MAPK1 axis ( Zhang et al, 2020 ). In this study, we found that circ_100395 was downregulated in lung cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, circRNA_101237 promotes NSCLC progression via the miRNA-490-3p/MAPK1 axis. 17 CircRNA BIRC6 promotes NSCLC cell progression by sponging microRNA-145. 18 Circ_0072088 promotes the development of NSCLC via the miR7/NOVA2 axis.…”
Section: Discussionmentioning
confidence: 99%